The Role of Automation and Platformization in Enhancing Enterprise Cybersecurity - Chintan Udeshi (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article examines the critical role of automation and platformization in addressing the challenges faced by modern enterprise cybersecurity. As organizations increasingly adopt hybrid and multi-cloud strategies, they find themselves managing a complex array of security tools, leading to overwhelming volumes of alerts and fragmented visibility. The paper explores how Security Orchestration, Automation, and Response (SOAR) technologies can streamline security operations by automating routine tasks, integrating disparate tools, and significantly reducing incident response times. Additionally, it discusses the trend towards platformization and vendor consolidation, highlighting the benefits of centralized threat visibility and consistent policy enforcement across diverse environments. The article argues that these approaches not only enhance an organization’s ability to detect and respond to threats but also allow security teams to focus on more advanced, high-priority issues. By presenting a comprehensive overview of these strategies, the paper provides valuable insights for organizations seeking to improve their cybersecurity posture in an increasingly complex digital landscape.